Contribution of the capsular polysaccharide layer to antibiotic resistance in bifidobacteria. Issue 4 (20th March 2023) - Argentini, Chiara; Tarracchini, Chiara; Alessandri, Giulia; Longhi, Giulia; Milani, Christian; van Sinderen, Douwe; Ventura, Marco; Turroni, Francesca
Abstract: Bifidobacteria have been shown to produce exopolysaccharides (EPS), which are polymeric structures composed of various carbohydrates, commonly containing glucose, galactose, and rhamnose. EPS are produced by different bifidobacterial taxa commonly identified in the human gut, such as Bifidobacterium breve and Bifidobacterium longum subsp. longum, and have been suggested to modulate the interaction of bifidobacterial cells with other members of the human gut microbiota as well as with their host. In this study, we evaluated if bifidobacterial EPS production of four selected EPS-producing strains is associated with enhanced resistance to antibiotic treatments through MIC analysis when compared to bacterial cultures that do not produce exopolysaccharides. Our results showed that an increase in EPS production by modifying the growth medium with different carbon sources, i.e. glucose, galactose or lactose and/or by applying stressful conditions, such as bile salts and acidity, is associated with a tolerance enhancement of bifidobacterial cells toward various beta-lactam antibiotics. In addition, after analyzing the production of EPS at the phenotypic level, we explored the genes involved in the production of these structures and evaluated their expression, in presence of various carbon sources, using RNAseq. Overall, this study provides preliminary experimental evidence showing how bifidobacterial EPS modifies the level of susceptibility of these bacteria towards antibiotics. Abstract : Potential involvment of bifidobacterial exopolysaccharides in antibiotic resistance.